Binder for lithium ion battery, preparation method of binder and lithium ion battery

By using modified maleic anhydride-acrylamide polymer as the binder in lithium-ion batteries, the problems of insufficient brittleness and elasticity of the existing binder are solved, and the cycle stability and processing performance of the battery are significantly improved.

CN119552604APending Publication Date: 2025-03-04SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411734019.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The binder used in existing lithium-ion batteries has high brittleness and poor elasticity, and cannot adapt to the volume changes generated by the silicon-based negative electrode during circulation, resulting in a reduction in battery cycle stability and safety.

Method used

Maleic anhydride and acrylamide are used for polymerization, and modified with nonaminonanoic acid to obtain a polymer rich in a variety of active functional groups such as amine groups, carboxyl groups, amides, etc. These functional groups provide self-healing function and good flexibility, improving the peel strength of the pole and electrode specific capacity stability.

Benefits of technology

The electrode stripping strength, circulation capacity retention rate and battery processing performance of the lithium-ion battery are significantly improved, and the expansion of the silicon negative electrode and cracking problems during the coating process are suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure FDA0005161021420000011
    Figure FDA0005161021420000011
Patent Text Reader

Abstract

The invention relates to a binder for a lithium ion battery, a preparation method of the binder and the lithium ion battery in the technical field of lithium battery production. The binder comprises a polymer; maleic anhydride and acrylamide are subjected to a polymerization reaction, nonamidononanoic acid is used for modification, and a long alkyl chain in the nonamidononanoic acid is utilized, so that a target polymer has good flexibility, the cracking problem in the coating process is inhibited, and meanwhile, the service life of the polymer is prolonged. The finally obtained target polymer is rich in various active functional groups such as amido, carboxyl and amide, and the functional groups provide a large number of active sites and have a self-repairing function, so that the peeling strength of a pole piece is improved, expansion of a silicon negative electrode in the circulation process is further inhibited, and the service life of the pole piece is prolonged. And the specific capacity stability of the electrode in the whole circulation process is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery production, and in particular to a binder for lithium ion batteries and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Binders play a key role in the preparation of lithium-ion battery electrodes. Although used in small amounts, they have a significant impact on the electrochemical and safety performance of the battery. Its core function is to ensure that the active material and the conductive agent are tightly attached to the current collector, maintain effective contact between the electrode and the current collector, and build an electron transfer network. At the same time, the binder promotes the transfer of lithium ions between the electrode and the electrolyte, stabilizes the structure of the active material, maintains appropriate porosity and overall connectivity, and alleviates volume changes during charging and discharging.

[0003] As the most commonly used negative electrode binder in lithium-ion batteries, CMC (sodium carboxymethyl cellulose) may crack during the coating process due to its brittleness. During the charging and discharging process of the battery, the pole piece may crack, resulting in reduced battery safety. In addition, during the tableting and slitting process of CMC, the graphite negative electrode may seriously lose powder, affecting battery performance. The stability problem of SBR (styrene-butadiene rubber): SBR is easy to demulsify under long-term stirring, thereby destroying its structure and reducing its adhesion. At the same time, the dispersion effect of SBR is not as good as CMC. Too much SBR will cause greater swelling, so SBR cannot be used completely as a binder. The flexibility problem of PAA (polyacrylic acid): There are a large number of strong polar functional groups such as carboxyl and hydroxyl in the molecular structure of PAA. Too many hydrogen bonds between these functional groups will hinder the free rotation of the molecular chain, making the polymer poor in flexibility, which is not conducive to bearing the stress generated by the volume expansion of the active substance, affecting the improvement of battery performance.

[0004] In order to solve the above problems, Chinese patent document with patent number CN118406451A provides a water-based adhesive and its preparation method and application. The technical solution included in the patent is to mix acrylic acid, maleic anhydride, acrylamide, sulfonic acid functional monomer, silane functional monomer, initiator and part of water, carry out polymerization reaction, add remaining water to the obtained polymerization product to adjust the viscosity to the target, and obtain the water-based adhesive. The strength and elasticity of the acrylic adhesive are improved by introducing sulfonic acid group and silane functional monomers.

[0005] This water-based adhesive can solve the problems of traditional adhesives to a certain extent. However, in actual use, the above technical solution still has defects such as coating cracking, unsatisfactory cycle performance, and insufficient peel strength.

[0006] Therefore, it is necessary to provide a binder for lithium ion battery negative electrode with better performance, which can be applied to lithium ion batteries so that it can improve the pole piece peeling strength, inhibit the expansion of silicon negative electrode during the cycle, improve the specific capacity stability of the electrode during the cycle, and at the same time have good flexibility to inhibit cracking during the coating process. Summary of the invention

[0007] In order to solve the above technical problems, the present invention discloses a binder for lithium-ion batteries and a preparation method thereof. The present invention uses maleic anhydride and acrylamide for polymerization reaction, and uses nonaminopelvic acid for modification. The obtained target polymer is rich in multiple active functional groups such as amine, carboxyl, and amide. These functional groups provide a large number of active sites and have self-repairing functions, thereby improving the peeling strength of the pole piece, further inhibiting the expansion of the silicon negative electrode during the cycle, and further improving the specific capacity stability of the electrode during the entire cycle. In addition, the alkyl chain in nonaminopelvic acid is relatively long, so that the target polymer has good flexibility and can inhibit the cracking problem during the coating process. The technical solution of the present invention is implemented as follows:

[0008] The first aspect of the present invention is to disclose a binder for lithium ion batteries, the molecular structure of which is as follows:

[0009]

[0010] The binder is polymerized by using maleic anhydride and acrylamide, and modified by using nonaaminononanoic acid. The longer alkyl chain in nonaaminononanoic acid is used to make the target polymer have good flexibility, and the cracking problem during the coating process is suppressed. At the same time, the target polymer finally obtained is rich in multiple active functional groups such as amine, carboxyl, and amide. These functional groups provide a large number of active sites and have self-repairing functions, thereby improving the peeling strength of the electrode, further suppressing the expansion of the silicon negative electrode during the cycle, and further improving the specific capacity stability of the electrode during the entire cycle.

[0011] The second aspect of the present invention discloses a lithium ion battery comprising the binder for lithium ion batteries, wherein the lithium ion battery has a composition of two or more binders, including a polymer binder of maleic anhydride and acrylamide modified with the nonaaminononanoic acid.

[0012] The third aspect of the present invention discloses a method for preparing a binder for lithium ion batteries, wherein maleic anhydride and acrylamide are used for polymerization, and nonaaminononanoic acid is used to modify the product of the polymerization reaction.

[0013] Preferably, the steps include:

[0014] Step S1, adding maleic anhydride and acrylamide to a solvent, mixing, heating to a first temperature and keeping it constant to obtain a first mixed solution, adding an initiator to the first mixed solution under nitrogen protection, heating to a second temperature, keeping the temperature for reaction, and then cooling to room temperature to obtain a second mixed solution;

[0015] Step S2, adding 9-aminononanoic acid to the second mixed solution, adding an amidation reagent under ice bath conditions, and reacting under ice bath conditions overnight to obtain a third mixed solution;

[0016] Step S3, pouring the third mixed solution into acetone to precipitate, filtering, washing the filter cake with acetone for 3 times, and vacuum drying to obtain a modified binder for lithium ion batteries.

[0017] Preferably, in step S1, the solvent is tetrahydrofuran (THF).

[0018] Preferably, in step S1, the first temperature is 65°C to 75°C.

[0019] Preferably, in step S1, the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate (AIBME).

[0020] Preferably, in step S1, the second temperature is 75°C to 85°C.

[0021] Preferably, in step S2, the amidation reagent includes 2-ethoxy-1-ethoxycarbonyl-1,2-dihydroquinoline (EEDQ).

[0022] The term "at least one" as used in the present invention means that one or more initiators can be selected from them. As long as these initiators do not chemically react with each other and do not react to the formation of the target substance, they can be freely selected according to needs. The present invention does not impose any restrictions on this.

[0023] The technical solution of the present invention can be implemented using any numerical value within the above numerical range, and the present invention does not impose any limitation on this.

[0024] Preferably, the molar ratio of the maleic anhydride, the acrylamide and the 9-aminononanoic acid is 1:0.8:0.1.

[0025] The advantages of the present invention are as follows:

[0026] The present invention uses maleic anhydride and acrylamide to carry out polymerization reaction, and uses nonaminopelvic acid for modification, and the obtained target polymer is rich in multiple active functional groups such as amine, carboxyl, amide, etc. These functional groups provide a large number of active sites, which help to improve the adhesion between the binder and the electrode material, thereby improving the peel strength of the pole piece. At the same time, the battery pole piece using the binder has a self-repairing function: the target polymer has a self-repairing function, which helps to repair microcracks caused by volume expansion or other mechanical stresses during the battery cycle, further inhibits the expansion of the silicon negative electrode during the cycle, and improves the specific capacity stability of the electrode. At the same time, the battery pole piece using the binder has good flexibility: because the alkyl chain in nonaminopelvic acid is relatively long, the target polymer has good flexibility, which can inhibit the cracking problem during the coating process and improve the processing performance and reliability of the battery. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.

[0029] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0030] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0031] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0032] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0033] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0034] Traditional lithium-ion battery negative electrode binders have certain performance limitations, such as high brittleness and poor elasticity. They cannot adapt to the large volume changes of silicon-based negative electrodes during cycling, affecting the long-term cycle stability of lithium batteries. For example, when CMC is used as a negative electrode binder, due to its brittleness, the electrode may crack during the battery's charge and discharge process, resulting in reduced battery safety. Another example is when PAA is used as a binder. There are a large number of strong polar functional groups such as carboxyl and hydroxyl in the PAA molecular structure. Excessive hydrogen bonds between these functional groups will hinder the free rotation of the molecular chain, making the polymer less flexible and not conducive to bearing the stress generated by the volume expansion of the active substance, affecting the improvement of battery performance.

[0035] In order to solve the above problems, the first aspect of the present invention proposes a binder for lithium-ion batteries, wherein the binder uses maleic anhydride and acrylamide for polymerization reaction and is modified with nonaaminononanoic acid. The target polymer obtained is rich in various active functional groups such as amine, carboxyl, and amide. These functional groups provide a large number of active sites and have self-repairing functions, thereby improving the peel strength of the electrode sheet and further inhibiting the expansion of the silicon negative electrode during the cycle, so that the specific capacity stability of the electrode during the entire cycle is further improved. In addition, the alkyl chain in the nonaaminononanoic acid is relatively long, so that the target polymer has good flexibility, which can inhibit the cracking problem during the coating process.

[0036] The embodiments of the present invention will be described in more detail below through examples and comparative examples. All examples and comparative examples are lithium ion battery sample groups prepared by the same process, and all processes and materials are exactly the same except for the binder.

[0037] In order to intuitively and comprehensively reflect the advantages of the present invention, all embodiments and comparative examples include pole piece peel strength test, battery initial charge and discharge efficiency test, battery discharge performance test under 3C rate condition at room temperature, 500-week battery cycle capacity retention rate test at room temperature, and cracking record during negative electrode coating process.

[0038] In addition, the embodiments of the present invention are not limited only to these Examples.

[0039] Example 1

[0040] 1. Preparation of Binder

[0041] S1, add 98.06g (1mol) of maleic anhydride and 56.86g (0.8mol) of acrylamide into a 2000mL three-necked flask equipped with an electric stirrer, a reflux condenser connected to a drying tube and a thermometer; add 1000mL of THF; stir to dissolve the contents; heat in a water bath until the temperature is constant at 70°C to obtain a first mixed solution; pass nitrogen protection, and then add 4.9g (5%, by mass) of azobisisobutyronitrile as an initiator; heat to 80°C and keep the temperature for reaction for 6 hours, then cool to room temperature to obtain a second mixed solution;

[0042] S2, adding 8.65 g (0.05 mol) of 9-aminononanoic acid to the second mixed solution, adding 37 g (0.15 mol) of an amidating agent, EEDQ, under ice bath conditions, and reacting overnight under ice bath conditions to obtain a third mixed solution;

[0043] S3, pouring the third mixed solution into acetone for precipitation; filtering, washing the filter cake with acetone for 3 times, and vacuum drying to obtain the target polymer ploymer-F, which is the binder.

[0044] 2. Preparation of negative electrode sheet

[0045] 2.2wt% of negative electrode binder (polymer ploymer-F), 96.4wt% of negative electrode active material silicon negative electrode, 1% of negative electrode conductive agent conductive carbon black, and 1.2wt% of thickener sodium carboxymethyl cellulose (CMC) were mixed, and deionized water was added for stirring to prepare a negative electrode composition. The negative electrode composition was then coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, a negative electrode sheet was obtained.

[0046] Record the coating conditions.

[0047] 3. Preparation of positive electrode

[0048] 97.4wt% of positive electrode active material lithium iron phosphate, 0.5wt% of positive electrode conductive agent conductive carbon black, 0.4wt% of positive electrode conductive agent carbon nanotubes, and 1.7wt% of positive electrode binder polyvinylidene fluoride were added to N-methylpyrrolidone and stirred to prepare positive electrode slurry. The positive electrode slurry was then coated on both surfaces of the positive electrode current collector A1 foil, and after drying, cold pressing, slitting and other processes, a positive electrode sheet was obtained.

[0049] 4. Lithium-ion battery preparation

[0050] Arrange the positive electrode sheet, isolation film (PE film), and negative electrode sheet in order, so that the isolation film is placed between the positive and negative electrodes to play an isolating role, to make an electrode assembly, place the electrode assembly in an outer package, inject commercially available electrolyte and seal it, and then go through processes such as liquid injection, formation, and exhaust to obtain a lithium-ion battery.

[0051] Example 2

[0052] 1. Preparation of Binder

[0053] S1, adding 98.06g (1mol) of maleic anhydride and 56.86g (0.8mol) of acrylamide into a 2000mL three-necked flask equipped with an electric stirrer, a reflux condenser connected to a drying tube and a thermometer; adding 1000mL of THF; stirring to dissolve the contents; heating in a water bath until the temperature is constant at 70°C to obtain a first mixed solution; passing nitrogen protection, and then adding 4.9g (5%, by mass) of azobisisobutyronitrile as an initiator; heating to 80°C and keeping the temperature for reaction for 6h, and then cooling to room temperature to obtain a second mixed solution;

[0054] S2, adding 17.3 g (0.1 mol) of 9-aminononanoic acid to the second mixed solution, adding 37 g (0.15 mol) of an amidating agent, EEDQ, under ice bath conditions, and reacting overnight under ice bath conditions to obtain a third mixed solution;

[0055] S3, pouring the third mixed solution into acetone for precipitation; filtering, washing the filter cake with acetone for 3 times, and vacuum drying to obtain the target polymer ploymer-F, which is the binder.

[0056] 2. Preparation of negative electrode sheet

[0057] 2.2wt% of negative electrode binder (polymer ploymer-F), 96.4wt% of negative electrode active material silicon negative electrode, 1% of negative electrode conductive agent conductive carbon black, and 1.2wt% of thickener sodium carboxymethyl cellulose (CMC) were mixed, and deionized water was added for stirring to prepare a negative electrode composition. The negative electrode composition was then coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, a negative electrode sheet was obtained.

[0058] Record the coating conditions.

[0059] 3. Preparation of positive electrode

[0060] 97.4wt% of positive electrode active material lithium iron phosphate, 0.5wt% of positive electrode conductive agent conductive carbon black, 0.4wt% of positive electrode conductive agent carbon nanotubes, and 1.7wt% of positive electrode binder polyvinylidene fluoride were added to N-methylpyrrolidone and stirred to prepare positive electrode slurry. The positive electrode slurry was then coated on both surfaces of the positive electrode current collector A1 foil, and after drying, cold pressing, slitting and other processes, a positive electrode sheet was obtained.

[0061] 4. Lithium-ion battery preparation

[0062] Arrange the positive electrode sheet, isolation film (PE film), and negative electrode sheet in order, so that the isolation film is placed between the positive and negative electrodes to play an isolating role, to make an electrode assembly, place the electrode assembly in an outer package, inject commercially available electrolyte and seal it, and then go through processes such as liquid injection, formation, and exhaust to obtain a lithium-ion battery.

[0063] Example 3

[0064] 1. Preparation of Binder

[0065] S1, adding 98.06g (1mol) of maleic anhydride and 56.86g (0.8mol) of acrylamide into a 2000mL three-necked flask equipped with an electric stirrer, a reflux condenser connected to a drying tube and a thermometer; adding 1000mL of THF; stirring to dissolve the contents; heating in a water bath until the temperature is constant at 70°C to obtain a first mixed solution; passing nitrogen protection, and then adding 4.9g (5%, by mass) of azobisisobutyronitrile as an initiator; heating to 80°C and keeping the temperature for reaction for 6h, and then cooling to room temperature to obtain a second mixed solution;

[0066] S2, adding 34.6 g (0.2 mol) of 9-aminononanoic acid to the second mixed solution, adding 37 g (0.15 mol) of an amidating agent, EEDQ, under ice bath conditions, and reacting overnight under ice bath conditions to obtain a third mixed solution;

[0067] S3, pouring the third mixed solution into acetone for precipitation; filtering, washing the filter cake with acetone for 3 times, and vacuum drying to obtain the target polymer ploymer-F, which is the binder.

[0068] 2. Preparation of negative electrode sheet

[0069] 2.2wt% of negative electrode binder (polymer ploymer-F), 96.4wt% of negative electrode active material silicon negative electrode, 1% of negative electrode conductive agent conductive carbon black, and 1.2wt% of thickener sodium carboxymethyl cellulose (CMC) were mixed, and deionized water was added for stirring to prepare a negative electrode composition. The negative electrode composition was then coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, a negative electrode sheet was obtained.

[0070] Record the coating conditions.

[0071] 3. Preparation of positive electrode

[0072] 97.4wt% of positive electrode active material lithium iron phosphate, 0.5wt% of positive electrode conductive agent conductive carbon black, 0.4wt% of positive electrode conductive agent carbon nanotubes, and 1.7wt% of positive electrode binder polyvinylidene fluoride were added to N-methylpyrrolidone and stirred to prepare positive electrode slurry. The positive electrode slurry was then coated on both surfaces of the positive electrode current collector A1 foil, and after drying, cold pressing, slitting and other processes, a positive electrode sheet was obtained.

[0073] 4. Lithium-ion battery preparation

[0074] Arrange the positive electrode sheet, isolation film (PE film), and negative electrode sheet in order, so that the isolation film is placed between the positive and negative electrodes to play an isolating role, to make an electrode assembly, place the electrode assembly in an outer package, inject commercially available electrolyte and seal it, and then go through processes such as liquid injection, formation, and exhaust to obtain a lithium-ion battery.

[0075] Example 4

[0076] 1. Preparation of Binder

[0077] S1, adding 98.06g (1mol) of maleic anhydride and 56.86g (0.8mol) of acrylamide into a 2000mL three-necked flask equipped with an electric stirrer, a reflux condenser connected to a drying tube and a thermometer; adding 1000mL of THF; stirring to dissolve the contents; heating in a water bath until the temperature is constant at 70°C to obtain a first mixed solution; passing nitrogen protection, and then adding 4.9g (5%, by mass) of azobisisobutyronitrile as an initiator; heating to 80°C and keeping the temperature for reaction for 6h, and then cooling to room temperature to obtain a second mixed solution;

[0078] S2, adding 51.9 g (0.3 mol) of 9-aminononanoic acid to the second mixed solution, adding 37 g (0.15 mol) of an amidating agent, EEDQ, under ice bath conditions, and reacting overnight under ice bath conditions to obtain a third mixed solution;

[0079] S3, pouring the third mixed solution into acetone for precipitation; filtering, washing the filter cake with acetone for 3 times, and vacuum drying to obtain the target polymer ploymer-F, which is the binder.

[0080] 2. Preparation of negative electrode sheet

[0081] 2.2wt% of negative electrode binder (polymer ploymer-F), 96.4wt% of negative electrode active material silicon negative electrode, 1% of negative electrode conductive agent conductive carbon black, and 1.2wt% of thickener sodium carboxymethyl cellulose (CMC) were mixed, and deionized water was added for stirring to prepare a negative electrode composition. The negative electrode composition was then coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, a negative electrode sheet was obtained.

[0082] Record the coating conditions.

[0083] 3. Preparation of positive electrode

[0084] 97.4wt% of positive electrode active material lithium iron phosphate, 0.5wt% of positive electrode conductive agent conductive carbon black, 0.4wt% of positive electrode conductive agent carbon nanotubes, and 1.7wt% of positive electrode binder polyvinylidene fluoride were added to N-methylpyrrolidone and stirred to prepare positive electrode slurry. The positive electrode slurry was then coated on both surfaces of the positive electrode current collector A1 foil, and after drying, cold pressing, slitting and other processes, a positive electrode sheet was obtained.

[0085] 4. Lithium-ion battery preparation

[0086] Arrange the positive electrode sheet, isolation film (PE film), and negative electrode sheet in order, so that the isolation film is placed between the positive and negative electrodes to play an isolating role, to make an electrode assembly, place the electrode assembly in an outer package, inject commercially available electrolyte and seal it, and then go through processes such as liquid injection, formation, and exhaust to obtain a lithium-ion battery.

[0087] Comparative Example

[0088] 1. Preparation of Binder

[0089] S1, adding 98.06g (1mol) of maleic anhydride and 56.86g (0.8mol) of acrylamide into a 2000mL three-necked flask equipped with an electric stirrer, a reflux condenser connected to a drying tube and a thermometer; adding 1000mL of THF; stirring to dissolve the contents; heating in a water bath until the temperature is constant at 70°C to obtain a first mixed solution; passing nitrogen protection, and then adding 4.9g (5%, by mass) of azobisisobutyronitrile as an initiator; heating to 80°C and keeping the temperature for reaction for 6h, and then cooling to room temperature to obtain a second mixed solution;

[0090] S2, pouring the third mixed solution into acetone for precipitation; filtering, washing the filter cake with acetone for 3 times, and vacuum drying to obtain a maleic anhydride-acrylamide copolymer.

[0091] 2. Preparation of negative electrode sheet

[0092] 2.2wt% of negative electrode binder (maleic anhydride-acrylamide copolymer), 96.4wt% of negative electrode active material silicon negative electrode, 1% of negative electrode conductive agent conductive carbon black, and 1.2wt% of thickener sodium carboxymethyl cellulose (CMC) were mixed, and deionized water was added for stirring to prepare a negative electrode composition. The negative electrode composition was then coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, a negative electrode sheet was obtained.

[0093] Record the coating conditions.

[0094] 3. Preparation of positive electrode

[0095] 97.4wt% of positive electrode active material lithium iron phosphate, 0.5wt% of positive electrode conductive agent conductive carbon black, 0.4wt% of positive electrode conductive agent carbon nanotubes, and 1.7wt% of positive electrode binder polyvinylidene fluoride were added to N-methylpyrrolidone and stirred to prepare positive electrode slurry. The positive electrode slurry was then coated on both surfaces of the positive electrode current collector A1 foil, and after drying, cold pressing, slitting and other processes, a positive electrode sheet was obtained.

[0096] 4. Lithium-ion battery preparation

[0097] Arrange the positive electrode sheet, isolation film (PE film), and negative electrode sheet in order, so that the isolation film is placed between the positive and negative electrodes to play an isolating role, to make an electrode assembly, place the electrode assembly in an outer package, inject commercially available electrolyte and seal it, and then go through processes such as liquid injection, formation, and exhaust to obtain a lithium-ion battery.

[0098] Comparative experiment:

[0099] Take 5 groups of samples from Examples 1-4 and Examples, each group has 20 samples, and perform the following tests respectively:

[0100] 1. Peel strength test

[0101] (1) First, use a flat paper cutter to cut the graphite negative electrode sheet into strips with a length of 170 mm and a width of 20 mm, and then wipe the scaleless steel ruler clean with dust-free paper to leave no stains or dust;

[0102] (2) Next, place a 25 mm wide double-sided tape on a scaleless steel ruler with a length of 70 mm in the center.

[0103] (3) Then, the test sample is pasted on the double-sided tape with the end faces flush, and a pressing wheel (2 kg) with a diameter of 84 mm and a height of 45 mm is used to roll back and forth on the surface of the electrode three times;

[0104] (4) After the free end of the negative electrode sheet in the experimental sample is folded 180°, it is clamped on the upper clamp of the tensile tester, and a scaleless steel ruler is clamped on the lower clamp. Under the conditions of 22-28°C and humidity less than 25%, several 20mm wide negative electrode sheets are prepared. The electrode sheet stretching speed is 200mm / min. The test takes the average value of the stretching of 25-80mm (total stretching distance 100mm), and the negative electrode sheet is peeled off. When the electrode sheet current collector and the coating are completely separated, the test result of the electrode sheet coating peeling strength is read.

[0105] 2. Battery first charge and discharge efficiency test

[0106] At room temperature, charge at 1 / 3C to the termination voltage, with a cut-off current of 0.05C, record the charge capacity, and let stand for 30 minutes;

[0107] Discharge at 1 / 3C to the termination voltage, record the discharge capacity, and use the ratio of the discharge capacity to the charging capacity to get the first charge and discharge efficiency.

[0108] 3. Battery discharge performance test at 3C rate under room temperature

[0109] At room temperature, charge at 1C to the final voltage, cut-off current 0.05C, let stand for 30 minutes, discharge at 1C and 3C to the final voltage, record the discharge capacity, and compare the 3C discharge capacity with the 1C discharge capacity to get the room temperature 3C rate discharge performance;

[0110] Capacity retention rate after 500 cycles at room temperature

[0111] (1) Charge at 1C or specified current to the final voltage, cut-off current 0.05C, and let stand for 30 minutes;

[0112] (2) Discharge at 1C to the final discharge voltage, record the discharge capacity, and let stand for 30 minutes; cycle (1)-(2)

[0113] The above data are all average values.

[0114] The final data from the above tests and the coating conditions recorded when preparing the battery are summarized in the following table.

[0115]

[0116] According to the above table, the use of maleic anhydride-acrylamide copolymer modified with 9-aminononanoic acid as a binder can significantly improve the pole piece peel strength test, the battery's first charge and discharge efficiency, the discharge performance, and the battery cycle capacity retention rate of lithium-ion batteries. In addition, due to the long alkyl chain in nonaaminononanoic acid, the target polymer has good flexibility, which can inhibit the cracking problem test during the coating process and the cracking during the negative electrode coating process.

[0117] According to Examples 1-3, when the molar ratio of maleic anhydride, acrylamide, and 9-aminononanoic acid is 1:0.8:0.1, the performance of the adhesive is the best.

[0118] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A binder for lithium ion batteries, characterized in that: Its molecular structure is as follows: Of these, 500 <m<1000,500<n<1000。 2. A lithium ion battery, characterized in that: The invention comprises the binder as claimed in claim 1, wherein the addition amount of the binder is 0.5wt%-5wt%.

3. The lithium ion battery according to claim 2, characterized in that The lithium ion battery further includes a second binder, which is different from the binder described in claim 1.

4. The lithium ion battery according to claim 3, characterized in that The lithium ion battery comprises a combination of two or more binders.

5. A method for preparing the binder for lithium ion batteries as claimed in claim 1, characterized in that: The binder is obtained by carrying out polymerization reaction with maleic anhydride and acrylamide and modifying the product of the polymerization reaction with amino fatty acid.

6. The method according to claim 5, characterized in that The preparation method comprises: Preparation of intermediate polymer: maleic anhydride and acrylamide are polymerized to form an intermediate polymer, Modification reaction: the intermediate polymer is subjected to a modification reaction with nonaaminononanoic acid, so that the epoxy groups in the intermediate polymer are ring-opened to form a compound containing multiple functional groups such as amine, carboxyl, amide, and hydroxyl.

7. The method according to claim 5, characterized in that The steps include: Step S1, adding maleic anhydride and acrylamide to a solvent, mixing, heating to a first temperature and keeping it constant to obtain a first mixed solution, adding an initiator to the first mixed solution under nitrogen protection, heating to a second temperature, keeping the temperature for reaction, and then cooling to room temperature to obtain a second mixed solution; Step S2, adding 9-aminononanoic acid to the second mixed solution, adding an amidation reagent under ice bath conditions, and reacting under ice bath conditions overnight to obtain a third mixed solution; Step S3, pouring the third mixed solution into acetone for precipitation, filtering, washing the filter cake with acetone and vacuum drying to obtain a modified binder for lithium ion batteries.

8. The method according to claim 7, characterized in that In the step S1, the solvent includes tetrahydrofuran (THF), the first temperature is 65°C to 75°C, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate (AIBME), and the second temperature is 75°C to 85°C.

9. The method according to claim 7, characterized in that: In the step S2, the amidation reagent includes 2-ethoxy-1-ethoxycarbonyl-1,2-dihydroquinoline (EEDQ).

10. The method according to claim 7, characterized in that The molar ratio of maleic anhydride, acrylamide and 9-aminononanoic acid is 1:0.8:0.1.

Citation Information

Patent Citations

  • Water-based binder as well as preparation method and application thereof

    CN118406451A